Surgical Treatment of Multiple Cardiac Valvular Disease - Fernández Perdomo, Gonzalo; Nozar, José V; Burstin, Jacobo; Estable, Héctor; Lorenzo, Alvaro; Abó, Juan C (Cirugía del Uruguay, 1980)
The Heart Surgery Department of the Hospital de Cl'inicas (University Medical School Hdspital) of Montevideo, presents its experience between 1976 and 1979, with 14 patients who underwent polivalvular surgery.